The Impact of Ownership Structure on Firms’ Dividend Policy: Evidence from JSE Listed Firms: Array - Peerbhai, Faeezah; Gumede, Bongumusa; Shabangu, Nompilo; Gumede, Nomshado; Ndhlovu, Njabulo; Hlomela, Tlholohelo (Acta Universitatis Danubius. Œconomica, 2021)
This study examines the impact of ownership structures on dividend policy for 89 firms listed on the Johannesburg Stock Exchange All Share Index (ALSI) from 2010 to 2019. To achieve this objective, three ownership structures were examined; the study employs a panel regression model to investigate this relationship incorporating both the fixed effects (FE) and random effects (RE) models. First, our result revealed that ownership is concentrated with institutional shareholders. Second, our FE model results show that managerial and foreign ownership structure has no relationship with firms' dividend policy. In contrast, the result shows a negative relationship between institutional ownership and dividend policy of firms in South Africa. Additionally, firm size and profitability have a positive relationship with the dividend policy. The South African ownership structure context is contrary to the agency theory where large shareholders use increase in dividend pay-out to reduce available earnings for the benefit of managers. It is evident from the results that institutional investors are active monitors of managers' performances. This study is the first in South Africa to the author's knowledge. Lastly, this study proffers key insight into the impact of ownership structures on dividend pay-out for investors seeking to invest in JSE stocks.